2019
DOI: 10.1103/physrevlett.123.126602
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Low-Field Colossal Magnetoresistance in Double-Perovskite Manganite

Abstract: The gigantic decrease of resistance by an applied magnetic field, which is often referred to as colossal magnetoresistance (CMR) 1-9 , has been an attracting phenomenon in strongly correlated electron systems. The discovery of CMR in manganese oxide compounds has developed the science of strong coupling among charge, orbital, and spin degrees of freedom. CMR is also attracting scientists from the viewpoint of possible applications to sensors, memories, and so on. However, no application using CMR effect has be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Such a low value of T N is at odds with previous neutron powder diffraction studies where the long-range AFM order was observed in the range 275-290 K [22,25]. In a later study the same authors, using a larger crystal, identified a series of superstructure peaks that were not compatible with the structure previously proposed and concluded that the NdBaMn 2 O 6 is isostructural with SmBaMn 2 O 6 and not compatible with an A-type magnetic ordering [26]. Therefore, the crystallographic and magnetic structures of NdBaMn 2 O 6 are now an open question.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Such a low value of T N is at odds with previous neutron powder diffraction studies where the long-range AFM order was observed in the range 275-290 K [22,25]. In a later study the same authors, using a larger crystal, identified a series of superstructure peaks that were not compatible with the structure previously proposed and concluded that the NdBaMn 2 O 6 is isostructural with SmBaMn 2 O 6 and not compatible with an A-type magnetic ordering [26]. Therefore, the crystallographic and magnetic structures of NdBaMn 2 O 6 are now an open question.…”
Section: Introductionmentioning
confidence: 56%
“…According to Ref. [26], NdBaMn 2 O 6 could be isostructural to SmBaMn 2 O 6 . Our study does not support this statement.…”
Section: Ndbamn 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneous catalysts [30]. High dielectric permittivity (ε), ferroelectricity, Electronic correlations [31][32][33][34][35][36] of such 3d states are generally strong, they have a more local character and a tendency for insulating states or metal-insulator transitions [37][38], magneto-resistance colossal [39], high capacity memory [40]. As a new generation of promising photovoltaic devices, perovskite solar cells (PSCs) have rapidly evolved in efficiency from 3.8% in 2009 to 23.5% recently [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…As the CMR effect is also often attributed to the Jahn-Teller (JT) effect [11], a parent compound of several important mixed-valence CMR manganite families, LaMnO 3 (LMO), is at the focus of intensive investigations [12,13]. Double perovskite-type manganites with a general formula AA BMnO 6 (where A and A are the rare earth or alkaline earth metals, and B is the d-block transition metals) also display a wide variety of interesting physical properties based on their compositional variations [14][15][16]. The usage of different dopants and changing the chemical make-up of manganites is focused on obtaining a material that can be used at room temperature and in a relatively low magnetic field.…”
Section: Introductionmentioning
confidence: 99%